Abundance, diversity and metabolic print of nematod communities in different life zones of the Huetar Norte region of Costa Rica - Varela Benavides, Ingrid (2018)
Soil biotic communities represent 25 % of the existing global diversity, therefore their study is important for their conservation and sustainable use. Among edaphic biota, nematodes are considered ecologically important as environmental indicators. Tools like the maturity indexes, food web diagnostics and metabolic footprints are used in assessing the ecosystem in relation to the impact contaminants and other stressors, as well as monitoring and measuring changes in the structure and dynamics of the food webs and, more recently, to study the impact of climate factors on the nematode community. Costa Rica is a tropical country with a variety of miroclimates in a small area; this attribute is reflected in the different life zones described by Holdridge for Costa Rica, which differ in their patterns of precipitation, temperature and evapotranspiration patterns. In this research, the diversity of climates was exploited in order to contribute with the knowledge of the nematode communities of several ecosystems within different life zones. For this purpose, samples were taken in several ecosystems located in different life zones in the Region Huetar Norte from Costa Rica. High variation in taxa abundance between different management types within ecosystems was obtained. However, the low availability of replicates for proper statistical analyzes made the mean estimations numerically unprovable. The maturity indexes and the food web diagnosis did not show statistical differences between the studied zones, while, the metabolic footprints were positively correlated to life zones. The metabolic footprint decreased in the different life zones in correspondence with the increase of the average annual temperature reported for each one. The metabolic footprints associated with the decomposition of organic matter (fungivores, bacterivores, and enrichment) had the strongest correlations. The proposition is that the increase in metabolic footprints while the temperature decreases, reflects a change in the dynamics of chemical and biological decomposition of organic matter and in the energy flow in the food networks. This research supports finding in other studies, suggesting that the temperature is a key factor in the species distribution in edaphic ecosystems, and therefore it should be subject to further investigation.